ANALYSIS RELATIONSHIP AMONG VISIONS, OLFACTIONS, TASTE, AND HAPTICS SENSE WITH SENSORY BRANDING FOR POND’S PRODUCT IN TONDANO - Pesik, Feronika (FEB Universitas Sam Ratulangi Manado, 2013)
There is one interesting fact that can be drawn from the general pattern of personal purchasing from all women in the world. Directly or indirectly, each important concept in delivering any product from cosmetics companies in the marketplace will be influenced, especially the following concept of Marketing, which is sensory marketing. Thus, this concept is influenced by visual, olfaction, taste and haptics senses, as seen from the marketing process for Pond’s products in the Tondano City. There are two important objectives in this research, which are: 1) To determine whether these Senses influence Sensory Branding for Pond’s Products in Tondano, simultaneously and 2) To determine whether each of these sense influence Sensory Branding for Pond’s Products in Tondano, partially. Both objectives will be later fulfilled by using Multiple Linear Regressions and four stated conclusions. This research is using quantitative methods. Data and information in this study were obtained from the result of questionnaires and from books, journals, and relevant literature from library and internet. The conclusions is, 1) These four Concepts generally give the significant influence for the dependent variable; 2) Only Vision Concept, Olfaction Concept and Haptics Concept have the significant influence for the changing of the dependent variable. There are two recommendations for representative management of Pond’s in Tondano City, which are: 1) more concerning about the importance of these four Concepts with the understanding of Sensory Marketing Concept of its products from people in the Tondano City; and 2) considering about other important factors that can impact the same Dependent Variable. Keywords: vision, olfaction, taste, haptics , sensory branding